Testowanie losowości procesu występowania wstrząsów w sejsmiczności naturalnej i sejsmiczności indukowanej pracami górniczymi - Letkowska, Magdalena (My University, 2009)
In M.Sc. thesis the character of the seismic event occurrence process in natural seismicity and seismicity induced by mining works was studied. The investigations were conducted based on data from an active seismogenic area of Greece and on series of mining seismic events from a Polish copper mine. The null hypothesis, assuming that the process of seismic event occurrence was Poissonian was verified. Two parameters were used: the difference between the empirical cumulative distribution of interevent time and the expotential distribution D(t), and the Matsumura’s coefficient of randomness. The bootstrap resampling technique was used for calculating confidence intervals of these parameters.

W pracy dyplomowej badano charakter procesu występowania wstrząsów w sejsmiczności naturalnej oraz sejsmiczności indukowanej pracami górniczymi. Badania prowadzono na danych pochodzących z aktywnych rejonów sejsmogenicznych Grecji oraz na seriach zjawisk sejsmicznych z polskiej kopalni rudy miedzi. W pracy weryfikowano hipotezę zerową, ?e proces występowania zjawisk sejsmicznych jest procesem Poissona. Do analiz wykorzystano parametry: D(t) określający różnicę pomiędzy empiryczną dystrybuantą odstępów czasu pomiędzy kolejnymi zdarzeniami, a dystrybuantą rozkładu wykładniczego oraz współczynnik losowości Matsumury. Do określenia przedziałów ufności wy?ej wymienionych parametrów wykorzystano techniki ponownego losowania bootstrap.
Randomness of the seismic event occurrence process in a natural seismicity and seismicity induced by mining works
Keywords: sejsmiczność indukowana; współczynnik losowości Matsumury; rozkład wykładniczy; bootstrap; induced seismicity; Matsumura’s coefficient of randomness; exponential distribution; bootstrap